MEMBUDAYAKAN PERMAINAN ENGKLEK BERBASIS ALAM (AMAZING LEARNING ATMOSPHERE MANAGEMENT): LITERASI TAMANSISWA UNTUK ANAK - Tiasari, Luky; Rochmiyati, Siti; Rezkita, Shanta (Universitas Padjadjaran, 2026)
Traditional activities such as Engklek hold substantial pedagogical potential in fostering children's creativity, motor skills, and literacy development. However, Demangan Village Park remains underutilized as a space for preserving and activating this cultural asset. The philosophical underpinning of Engklek, known as Zondag Maandag, symbolizes the human struggle for a dignified life and a better future (Syaripuddin, 2020) and embodies character values that are highly relevant to early childhood education. This philosophy serves as the foundation for a character- and culture-based community engagement program. The implementing team adopted a Community-Based Research (CBR) approach, structured through phases of initiation, socialization, training (six action cycles), evaluation, and reflection, all framed within the ALAM model (Amazing Learning Atmosphere Management). Replanted in the soil of Tamansiswa philosophy, Engklek evolved into a joyful learning garden where children internalized character values, practiced emotional regulation, explored language, and engaged with technology in meaningful ways. The intervention yielded a 90% positive impact across social, cultural, economic, and environmental dimensions. Five core values—honesty, discipline, responsibility, calmness, and patience—were cultivated through the activities and documented in the educational booklet ALAMku SEMANGATku. Overall, the program demonstrates that revitalizing traditional games through local philosophical frameworks can serve as an effective medium for nurturing children's character literacy in public village spaces.Aktivitas tradisional seperti Engklek menyimpan potensi pedagogis yang signifikan dalam mengembangkan daya cipta, keterampilan motorik, dan kapasitas literasi anak. Sayangnya, Taman Desa Demangan belum dimanfaatkan sebagai ruang pelestarian permainan tersebut. Filosofi Engklek, Zondag Maandag, yang bermakna perjuangan manusia untuk menjalani kehidupan layak demi masa depan yang lebih baik (Syaripuddin, 2020), merefleksikan nilai-nilai karakter yang relevan dengan pendidikan anak. Filosofi ini menjadi pijakan dalam merancang program pengabdian berbasis karakter dan budaya lokal. Tim pengabdi menerapkan metode Community Based Research (CBR) melalui tahap inisiasi, sosialisasi, pelatihan (6 aksi), evaluasi, dan refleksi berbasis ALAM (Amazing Learning Atmosphere Management). Engklek yang ditanam ulang dalam tanah filosofi Tamansiswa tumbuh menjadi taman belajar yang mengembirakan di mana anak-anak menyerap nilai karakter, mengelola emosi, bermain dengan bahasa, dan menyentuh teknologi dengan rasa. Permainan ini memberikan dampak positif sebesar 90% di aspek sosial, budaya, ekonomi, dan lingkungan. Lima nilai utama yaitu jujur, disiplin, tanggung jawab, tenang, dan sabar ditanamkan sebagai hasil kegiatan dan dikemas dalam buku ALAMku SEMANGATku. Keseluruhan kegiatan menunjukkan bahwa revitalisasi permainan tradisional berbasis filosofi lokal dapat menjadi medium efektif dalam membentuk literasi karakter anak di ruang publik desa.